Addressing Drop Outs From Early Grades At The Primary School Level By Strengthening Early Childhood Education In Singapore - Irwilda H. Bay; Arifin Suking; Roskina Mas (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
The problem in this study is how is the quality of education set by the Singapore Ministry of Education to realize the excellence of students at every level of education? How to develop early education to overcome the drop out at the primary school education level in Singapore? The method used in this study is a qualitative descriptive method. Data collection techniques through library studies. Literature research is a data collection technique by reviewing books, literature, notes, and various reports related to the problem to be solved. Data analysis techniques are carried out by reducing, presenting, and inferring the data that has been collected. The results showed that (1) The quality of education at every level and unit of education in Singapore has always been of particular concern to the Singapore Ministry of Education. Singapore's Ministry of Education always oversees the development of the national curriculum to obtain the desired Educational outcomes. in the form of student excellence in life skills, knowledge skills, and subject discipline knowledge organized into eight core skills and values: character development, self-management skills, social and cooperative skills, literacy and numeracy, communication skills, information skills, thinking skills and creativity, and skills of application of knowledge. (2) Singapore is a barometer of early childhood education programs in the Asia Pacific Region. The involvement of parents in supporting children's learning activities at home is a must so that the child's learning atmosphere while at school is supported and strengthened by the learning atmosphere at home.Keywords: education system, early childhood, Singapore, Schools, singapore